Novel red blood cell shaped α-Fe2O3 microstructures and FeO(OH) nanorods as high capacity supercapacitors. Issue 111 (26th October 2015) - Liu, Rongmei; Jiang, Zixiang; Liu, Qi; Zhu, Xiandong; Liu, Li; Ni, Lu; Shen, Chengcheng
Abstract : Novel red blood cell shaped α-Fe2 O3 microstructures were first synthesized through a hydrothermal method by using NH4 Cl as a structure-directing agent. Abstract : In this paper, we report the synthesis of novel red blood cell shaped α-Fe2 O3 microstructures for the first time, which were synthesized by using urea as a hydrolysis agent, ammonium chloride as a structure directing agent and PVA as a surfactant through a hydrothermal method. By only adjusting the hydrothermal temperature, FeO(OH) nanorods were obtained. When used as electrode materials in supercapacitors, the FeO(OH) nanorods exhibit much better capacitive properties of 392.6 F g −1 than red blood cell shaped α-Fe2 O3 microstructures (118.1 F g −1 ) at a current density of 1 A g −1, maintaining 91.4% and 75.5% of the initial capacity at a current density of 1 A g −1 after 500 cycles respectively. Such high performance can be attributed to the desirable morphology and components. The results manifest that the FeO(OH) nanorods may be promising electrode materials for supercapacitors.